A Study on Measuring Financial Literacy among Young Employees in Coimbatore City - Sekar, M.; Gowri, M. (Gyan Management Journal, 2015)
Today we rely on information through communication technologies and devices, which have brought a  great change in our life styles. This would have not been imagined before tlvo decades. It has influenced  the way we live and work. Therefore the set of skills required to get adapted to the new and dynamic  society is different. To participate and avail the benefits out of this technologically dependent society  ½as made the individuals acquire knowledge and skills required to get connected with the society .  . "inancial firms offer their clients a variety of products, many of which are new and often fairly complex.  :he reforms introduced in financial markets have reduced the scope of governments and employers in  :,upporting the employees to plan their future financial needs. So, the responsibility of managing and  ieciding their future financial needs has become a burden to the individuals. High job insecurity,  :mcertain income and easy access to consumption credit have a great influence on their financial  ::iehaviour. This shows the importance of financial literacy~inancial literacy is the mix of one's knowledge, skill and attitude towards financial matters. It helps to  '"'la ke informed decisions and well being of an individual. This study focuses on financial literacy  ::.mong young employees and to examine how well-equipped they are to make financial decisions. An  :;_ :tempt has been made through this study to measure the level of financial literacy of young employees.  _:::ndings of the study depict that gender, education, income and age impacts the level of financial ::eracy. This study would help in adopting appropriate strategies to improve the level of financial  :eracy amongst the young employees.
Keywords: Financial Literacy; Financial decisions; financial needs